1995
DOI: 10.1093/jnci/87.13.991
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancer in Relatives of Prostate Cancer Probands

Abstract: Background: It is estimated that there will be more than 244 000 new prostate cancer cases diagnosed and that more than 40 000 men will die of this disease during 1995. Evidence exists for a hereditary predisposition to prostate cancer, but the propor tion of cases attributable to the inheritance of a specific gene or genes is not large. Some hereditary cancer syndromes in volve more than one tumor site, and some studies have reported a familial association between prostate cancer and other cancers. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 7 publications
3
78
1
2
Order By: Relevance
“…A study from Washington state reported only one prostate cancer case with a germline BRCA1 mutation (185delAG) with a questionable family history, and an additional five rare allelic polymorphisms in other familial prostate cancer cases (Langston et al, 1996). An additional study failed to identify an increased risk of breast cancer in relatives of patients with prostate cancer (Issacs et al, 1995). One BRCA1 germline mutation carrier with CaP and familial cancer was reported among 24 Japanese CaP patients, no 185delAG or 6174delT mutation carriers were detected among 60 Ashkenazi CaP patients (Lehrer et al, 1998), and one 6174delT BRCA2 mutation carrier was found among 47 Jewish Ashkenazi individuals from 18 families with familial CaP (Wilkens et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…A study from Washington state reported only one prostate cancer case with a germline BRCA1 mutation (185delAG) with a questionable family history, and an additional five rare allelic polymorphisms in other familial prostate cancer cases (Langston et al, 1996). An additional study failed to identify an increased risk of breast cancer in relatives of patients with prostate cancer (Issacs et al, 1995). One BRCA1 germline mutation carrier with CaP and familial cancer was reported among 24 Japanese CaP patients, no 185delAG or 6174delT mutation carriers were detected among 60 Ashkenazi CaP patients (Lehrer et al, 1998), and one 6174delT BRCA2 mutation carrier was found among 47 Jewish Ashkenazi individuals from 18 families with familial CaP (Wilkens et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…A recent epidemiological analysis by Isaacs et al (1995) failed to identify a significantly increased risk of breast cancer among relatives of prostate cancer patients. Our findings are consistent with the findings of Isaacs et al Furthermore, there is no evidence of genetic linkage between BRCA1 and prostate cancer in high risk families (Eastman, 1996;Stephenson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…203 The association of PC with other cancers is not straightforward, as some studies confirm it 190,208,209 and others do not. 210,211 McCahy et al, 208 found an increase in breast cancer but no increase in ovarian cancer in relatives of PC probands. Introduction of 17q through microcell-mediated chromosome transfer has indicated a TSG for PC in a region of 28 cM (centi-Morgans) at 17q12-22 that includes BRCA1.…”
Section: Brca1 and Brca2 Tsgmentioning
confidence: 99%